1991
DOI: 10.1037/h0079071
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal behavior moderates "kindness norm" effects on cognitive and affective reactions to physical disability.

Abstract: Subjects viewed a videotaped interview of a confederate who appeared to be either with or without a physical disability, and who enacted either depressed or socially appropriate roles. Subjects were also told either they could choose to meet the target, they had to meet the target immediately following the tape, or nothing in regards to meeting the target. Results indicated that subjects reported higher levels of negative mood when they expected to meet the target, and depressed targets elicited higher rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Our research provides guidance on the contrasting perspectives surrounding the outcomes of stereotypes. While some researchers have found negative consequences can arise due to a group’s categorization as lower status (Elliott et al, 1991; Gershaw, 1996; Hastorf et al, 1979), others have identified no such differences (Colella et al, 1997; Fiske et al, 2002; Ren et al, 2008; Stone & Colella, 1996; Weiner et al, 1988). Our studies help to inform when expectations might transform into less favorable outcomes by recognizing a specific observed behavior, the act of negotiating by those with disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research provides guidance on the contrasting perspectives surrounding the outcomes of stereotypes. While some researchers have found negative consequences can arise due to a group’s categorization as lower status (Elliott et al, 1991; Gershaw, 1996; Hastorf et al, 1979), others have identified no such differences (Colella et al, 1997; Fiske et al, 2002; Ren et al, 2008; Stone & Colella, 1996; Weiner et al, 1988). Our studies help to inform when expectations might transform into less favorable outcomes by recognizing a specific observed behavior, the act of negotiating by those with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…This form of prejudice provokes perceptions that a person with a disability is neither prone nor capable of inflicting harm on the goals and members of higher status groups and may cause feelings of pity, promoting compassion, sympathy, and even tenderness toward those with disabilities (Fiske et al, 2002; Sevillano & Fiske, 2019). Such emotions further evoke feelings of superiority and a tendency toward caretaking in perceivers as they view those with disabilities as victims of their poor outcomes (Louvet, 2007; Stone & Colella, 1996), also known as the “norm to be kind” (Hastorf et al, 1979) or “kindness-to-the-handicapped” (Elliott et al, 1991; Gershaw, 1996). Applying the stereotype content model to a negotiation context, hiring managers might view job candidates with disabilities as weak and requiring help.…”
Section: Disability Stereotypes and Starting Salarymentioning
confidence: 99%
“…Subjects endorse more stereotypic beliefs about people with disability after exposure to a depressed person with disability while others viewing a nondepressed person with disability report significantly more open, accepting attitudes toward those with disability . Socially skilled persons with disability who exhibit assertive behavior are positively evaluated by subjects (Elliott, MacNair, Yoder, & Byrne, 1991). Unfortunately, this program of research has been confined to analogue designs, precluding any strong extrapolation to actual interactions between persons with and without disability.…”
mentioning
confidence: 99%